Determination of the effect of thickness reduction ratio, die angle, and coefficient of friction on residual stresses in ironing process: an analysis using computer simulation - Faizin, Akhmad; I Made Londen, Batan; Pramono, Agus Sigit; Wahjudi, Arif (Eastern-European Journal of Enterprise Technologies, 2021)
Ironing is a part of the group of metal forming processes, the process of reducing the thickness of the wall of a cup-shaped product. External load required to process metal forming, can cause residual stress. Residual stress can be beneficial or detrimental depending on the function of the product, the magnitude, and direction of the residual stress. Residual stress can act as an additional load on a given load. Residual stress can affect product quality, namely: dimensional accuracy, surface roughness, and mechanical properties. The speed of the ironing process is strongly influenced by the mechanical properties of the cup material, Thickness Reduction Ratio (TRR), and press tool design. The ironing process has a limited TRR value and if it is exceeded it results in product damage. Various studies on ironing were carried out to obtain an optimal process. In this research, stress analysis was carried out using the ANSYS software modeling simulation to obtain the occurring residual stress during the ironing process. The analysis was carried out by varying the TRR from 20 % to 30 %, the die angle from 25° to 30°, and the coefficient of friction from 0.05 to 0.15. Furthermore, processing and analysis of the stress analysis data are carried out to obtain the most dominant variables affecting the residual stress and the variable value that produces the lowest residual stress. Stress analysis was carried out on AA1100 aluminum cups with an outer diameter of 37 mm, a height of 20 mm, and a wall thickness of 2 mm. The results show that TRR and coefficient of friction are the most dominant variables affecting residual stress, while die angle has no significant effect. The lowest residual stress occurs at TRR 30 % and coefficient of friction 0.15